2010
DOI: 10.1159/000272059
|View full text |Cite
|
Sign up to set email alerts
|

Functional Characterization of a Partial Loss-of-Function Mutation of the Epithelial Sodium Channel (ENaC) Associated with Atypical Cystic Fibrosis

Abstract: Loss-of-function mutations of the epithelial sodium channel (ENaC) may contribute to pulmonary symptoms resembling those of patients with atypical cystic fibrosis (CF). Recently, we identified a loss-of-function mutation in the α-subunit of ENaC (αF61L) in an atypical CF patient without mutations in CFTR. To investigate the functional effect of this mutation, we expressed human wild-type αβγ-ENaC or mutant α F61Lβγ-ENaC in Xenopus laevis oocytes. The αF61L mutation reduced the ENaC mediated whole-ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 55 publications
1
26
0
Order By: Relevance
“…Human, mouse, and rat are indicated as h, m, and r, respectively. severity in individuals with one or two mutant CFTR alleles as suggested by others (2,20,33).…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Human, mouse, and rat are indicated as h, m, and r, respectively. severity in individuals with one or two mutant CFTR alleles as suggested by others (2,20,33).…”
Section: Discussionmentioning
confidence: 64%
“…These include SNPs, INDELs, and microsatellite repeats. Aside from a small number of variants (2,16,20,33,36,43), the functional properties of the vast majority of these ENaC variants are unknown.…”
Section: Epithelial Namentioning
confidence: 99%
“…Corresponding I/V plots (Fig. 1D) indicate that the tripletagged channel has a single-channel conductance (5.2 pS) that is typical for WT human ENaC (17,26). We also investigated the ion selectivity of the triple-tagged channel.…”
Section: Resultsmentioning
confidence: 90%
“…It has also been demonstrated that manipulations that result in a maximum increment in opening kinetics were capable of abolishing selfinhibition, for example, serine protease proteolysis and locking all channels in the open state (b S520C , a degenerin mutant). A mutation (a F61L ) at the amino terminal of the protein, adjacent to the gating tract in the M1 domain, enhanced self-inhibition (25). Our current understanding of the nature of ENaC gating mechanisms provides no unequivocal answers to the question of how the aforementioned domains affect self-inhibition.…”
Section: Epithelial Namentioning
confidence: 99%